GAMBARAN ASPEK FASILITAS SANITASI LIGKUNGAN DI SEKOLAH DASAR INPRES LANSOT - Kobis, Ifka Wangi (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Environmental sanitation is an important component in maintaining health. Schools are places where students or children gather, many activities carried out pose a threat of disease transmission if school cleanliness is not managed well. The function of the school as a learning facility also plays a role in relation to school sanitation, if sanitation facilities are inadequate it will affect the health status of students. This research aims to determine the description of the condition of sanitation facilities at Inpres Lansot Elementary School. This type of research is qualitative with observation techniques and in-depth interviews. The sample in this study were all teachers from the Inpresn Lansot Elementary School. The results of the research show that the condition of the clean water supply facilities, latrine facilities, waste disposal facilities and waste water disposal facilities at the Inpres Lansot Elementary School meets the requirements. Suggestions are expected to maintain clean water facilities, toilet facilities and waste disposal facilities in order to create a clean school environment and avoid various types of diseases.